Economic optimization of parallel and series configurations of the double effect absorption refrigeration system. (15th April 2020) - Arshad, Muhammad Umer; Zaman, Muhammad; Rizwan, Muhammad; Elkamel, Ali
Highlights: Optimization of series and parallel configurations of absorption refrigeration system. All the possible decision variables are optimized by incorporating all the necessary constraints. Total annual cost was reduce by 33.48% and 26.26% for the series and the parallel configuration, respectively. Both the solution heat exchangers were eliminated from the both series and parallel configurations. Abstract: Utilization of waste or low grade energy can significantly contribute to the world's energy demand and reduction of carbon dioxide emissions by employing absorption refrigeration systems. One of the major concerns linked with absorption refrigeration is its low efficiency and high capital cost. In present work, the objective was to develop an economic model for absorption refrigeration system adopting a previously validated thermodynamic model and optimize both the parallel and series configurations. The Thermodynamic and economic model was implemented in MATLAB®. The decision variables including temperatures of all the units of both configurations of absorption refrigeration system, outlet temperatures of cooling water, outlet temperature of chilled water, distribution ratio for parallel configuration and effectiveness of solution heat exchangers were optimized by cost minimization using Genetic Algorithm. All the required constraints, especially the crystallization enthalpy limit, were also included in the optimization problem to discard solutions which were not physically valid. The total annual cost was reduced by 33.48% and 26.26% for series and parallel configuration, respectively. Both solution heat exchangers were eliminated from the flow sheet of both configurations. Thermodynamic and economic performance at optimal operating conditions was found almost same for both configurations.